Gender Identification and the Fear of Crime: Do Masculinity and Femininity Matter in Reporting Fear of Crime?. Issue 1 (2nd January 2021) - Choi, Jaeyong; Merlo, Alida V.
ABSTRACT: Criminologists have been interested in the gap in reported levels of fear of crime between men and women for decades. Our study advances and empirically tests the hypothesis that gender identity is an important mechanism that accounts for the gap in fear of crime between men and women. Specifically, the current study incorporates Magliozzi, Saperstein, and Westbrook's gradational measures of masculinity and femininity to test if these variables are related to fear of crime. Statistical analyses reveal that masculinity is negatively and significantly associated with fear of crime, suggesting that men may be doing gender in reporting fear of crime by suppressing their expression of fear when responding to survey items related to fear of crime. Additionally, the inclusion of the measures of masculinity and femininity in our statistical model reduces the effect of sex to non-significance.